2018
DOI: 10.3390/bios8030068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Dental Implant Stability During Follow-Up: What Is Actually Measured, and Perspectives

Abstract: The optimization of loading protocols following dental implant insertion requires setting up patient-specific protocols, customized according to the actual implant osseointegration, measured through quantitative, objective methods. Various devices for the assessment of implant stability as an indirect measure of implant osseointegration have been developed. They are analyzed here, introducing the respective physical models, outlining major advantages and critical aspects, and reporting their clinical performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 76 publications
(94 reference statements)
1
53
0
1
Order By: Relevance
“…There are many examples of clinical problems that went through from a qualitative assessment to a quantitative evaluation thanks to their modelling [1], [2], furthermore, the application of classical experimental methods of structural analysis to the evaluation of the efficacy of procedures or surgical techniques [3]- [7] or to the evaluation of the mechanical characteristics of the materials used at different scales of investigation [8]- [10] pushed the dental science forward.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of clinical problems that went through from a qualitative assessment to a quantitative evaluation thanks to their modelling [1], [2], furthermore, the application of classical experimental methods of structural analysis to the evaluation of the efficacy of procedures or surgical techniques [3]- [7] or to the evaluation of the mechanical characteristics of the materials used at different scales of investigation [8]- [10] pushed the dental science forward.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that variations in implant surface characteristics and performance of osteotomy and implant placement by multiple operators may yield varying results in terms of ISQ measurement. This should be considered since previous studies compared the implant initial stability for tapered with cylindrical designed implants placed in vitro in bone blocks by investigators with varying skill and showed that the experienced clinicians achieved higher ISQ values with tapered‐implants in artificial bone blocks with varying densities. However, from a clinical perspective, it is hypothesized that narrow diameter implants when placed in dense bone (such as in the anterior mandible) remain functionally stable and demonstrate high ISQ values.…”
Section: Discussionmentioning
confidence: 99%
“…Histolojik analiz kemik-implant kontak miktarının hesaplanması için implant çevresindeki kemikten örnek alınmasını gerektirdiğinden oldukça invaziv bir yöntemdir. Bu nedenle, osseointegrasyon seviyesinin belirlenmesinde yüksek doğruluk payı olmasına rağmen klinik olmayan çalışmalarda ve deneylerde kullanılabilir [13].…”
Section: Histolojik Analizunclassified